2023
DOI: 10.3390/electronics12122555
|View full text |Cite
|
Sign up to set email alerts
|

A Patch Antenna with Enhanced Gain and Bandwidth for Sub-6 GHz and Sub-7 GHz 5G Wireless Applications

Abstract: This paper presents a novel microstrip patch antenna design using slots and parasitic strips to operate at the n77 (3.3–4.2 GHz)/n78 (3.3–3.8 GHz) band of sub-6 GHz and n96 (5.9–7.1 GHz) band of sub-7 GHz under 5G New Radio. The proposed antenna is simulated and fabricated using an FR-4 substrate with a relative permittivity of 4.3 and copper of 0.035 mm thickness for the ground and radiating planes. A conventional patch antenna with a slot is also designed and fabricated for comparison. A comprehensive analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…As a result of this comparison, a considerable improvement in the antenna gain is discovered, along with an acceptable size reduction. 3.5 GHz 1.88 [11] 3.5 GHz 5.3 [16] 3.6 GHz 2.52 [18] 3.5 GHz 4.2 [28] 3.5 GHz 4.57 4.90 5 [31] 3.5 GHz 6.05 [34] 3.5 GHz 5.43 [35] 3.29 GHz 3.38 [36] 3.36 GHz 1.07 [37] 3.5 GHz 5.8 [38] 3.45 GHz 3.83 [40] 3.5 GHz 4.28 [41] 3.45 GHz 4.64 [42] 3.5 GHz 3.338 4.66 5.08 This work 3.5 GHz 6.02 6. CONCLUSION A 3.5 GHz microstrip patch antenna has been designed in the said paper.…”
Section: Results Analysismentioning
confidence: 99%
“…As a result of this comparison, a considerable improvement in the antenna gain is discovered, along with an acceptable size reduction. 3.5 GHz 1.88 [11] 3.5 GHz 5.3 [16] 3.6 GHz 2.52 [18] 3.5 GHz 4.2 [28] 3.5 GHz 4.57 4.90 5 [31] 3.5 GHz 6.05 [34] 3.5 GHz 5.43 [35] 3.29 GHz 3.38 [36] 3.36 GHz 1.07 [37] 3.5 GHz 5.8 [38] 3.45 GHz 3.83 [40] 3.5 GHz 4.28 [41] 3.45 GHz 4.64 [42] 3.5 GHz 3.338 4.66 5.08 This work 3.5 GHz 6.02 6. CONCLUSION A 3.5 GHz microstrip patch antenna has been designed in the said paper.…”
Section: Results Analysismentioning
confidence: 99%
“…Different applications have been shown by patch antennas. Because of their being light weight, having a low profile and efficient radiation, they are being tried for 5G systems and even 6G communication [8] [63]. In medical diagnosis among other fields, patch antennas of dual bands are designed to work at specified frequencies like 2.4 GHz and 3.33 GHz through slot configuration [17].…”
Section: Future Directionsmentioning
confidence: 99%
“…For instance, a study by Nassr and Khamiss proposed a patch antenna at 38 GHz with enhanced gain and reduced side lobes to meet the demands of 5G communication [7]. Additionally, Jusoh's research demonstrated the design of a novel patch antenna operating at sub-6 GHz and sub-7 GHz bands, showcasing wider bandwidth and improved gains compared to conventional designs [8]. Yoo and Son introduced a millimeter-wave patch antenna that Disclaimer/Publisher's Note: The statements, opinions, and data contained in all publications are solely those of the individual author(s) and contributor(s) and not of MDPI and/or the editor(s).…”
Section: Introductionmentioning
confidence: 99%
“…The designed antenna has a frequency range that ranges from 3.8-4.4 GHz and the gain of 12.1 dB at 4.148 GHz [3]. With gain of 3.83 and 0.576 dB, antenna described in [4] has a broader BW of 160 MHz at 3.45 GHz and 220 MHz at 5.9 GHz. A sixteen element Ku/Ka-band multi-polarized antenna patch is built, and experimental results shows that impedance bandwidth of 19.4% (14.4-17.5 GHz) for dual linearly polarized (LP) and 7.4% (32.5-35 GHz) for dual circularly polarized (CP) may be achieved.…”
Section: Introductionmentioning
confidence: 99%